Jeffrey Gitomer's Little Book Of Leadership : The 12.5 Strengths Of Responsible, Reliable, Remarkable Leaders That Create Results, Rewards, And Resilience - Gitomer, Jeffrey H., author 428721; Hersey, Paul, editor 427199 (Hoboken, N. J. : John Wiley & Sons Inc., 2011)
What makes a leader relevant? It's not their place of employment, job title, experience, or status in life?it's their resilience. The true measure of any leader is his or her ability to react based on past experience and gut feelings, respond in real time to current circumstances, and then to recover quickly and move on with new lessons learned. The Little Book of Leadership combines classic style with the latest innovations to challenges the reader to self-evaluate every facet of their leadership, coaching, and communication abilities in order to better formulate what actions can be taken to improve their natural skills. Ideas and answers are provided for every challenge.